2021
DOI: 10.1108/ijcthr-08-2020-0189
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of tea traditions and impacts on tourism: the East Frisian tea culture

Abstract: Purpose The purpose of this study, a case study, is to present the uniqueness of the only UNESCO-awarded tea consumption tradition worldwide and its implications on the tourism industry by analyzing and weighting initializing effects of tea on the regional economy, as well tea tourism-related cultural and social rootings. Design/methodology/approach Between 20 July 2020 and 20 August 2020, qualitative interviews have been conducted with regional experts, as well as relevant statistics have been evaluated, cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Marital relationships play a role in shaping customers' tea preferences, impacting their selection when it comes to this beverage. Studies revealed an increased inclination for tea consumption among those in marital relationships [42]. The growing prominence of tea in India represents an avenue for visitors to delve into the intricacies of the country's diverse eating habits and cultural tapestry.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Marital relationships play a role in shaping customers' tea preferences, impacting their selection when it comes to this beverage. Studies revealed an increased inclination for tea consumption among those in marital relationships [42]. The growing prominence of tea in India represents an avenue for visitors to delve into the intricacies of the country's diverse eating habits and cultural tapestry.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Furthermore, tea has taken a variety of forms in different cultures (Jolliffe, 2007). Therefore, previous research established tea as a strong area of research as tea traditions combine tourists with cultural heritage (Bohne, 2021). Furthermore, tea cultivation plays an important role in reducing the impact of urbanization and strengthening biodiversity (Wu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, it is imperative to acknowledge the profound implications of tea tourists' perceptions, which transcend mere escapism and mood elevation. Tea tourism serves as an avenue for tourists to immerse themselves in traditional tea culture [19], thereby enriching their cultural identity [8,9]. By delving into the cultural facets of tea tourism, tourists not only escape from their bustling lives and attain a deeper understanding of tea culture but also forge a more profound emotional bond with tea tourism sites [20,21], thus contributing to both economic and cultural growth of the sustainable tea tourism.…”
Section: Introductionmentioning
confidence: 99%